PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, AKTIVITAS DAN NILAI PASAR TERHADAP RETURN SAHAM - Rusadi, Putri Lita; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACT The purpose of this study examines the effect of Return on Assets, Current Ratio, Debt Equity Ratio, Total Asset Turnover and Earnings per Share to return stock in companies that go public in Indonesia Stock Exchange. The method of selecting the purposive sampling technique against 28 companies from the consumer goods industry sector consisting of 112 observations financial statements for the period 2012-2015.The results of the study with multiple linear regression analysis states that in return on assets, the Current Ratio and Total Asset Turnover significant positive effect on stock returns. While the variable Debt Equity Ratio significant negative effect on stock returns and variable Earning per Share positive effect on stock returns, but not significant. Results of R Square (R2) indicates the number 0.931 or 93.1% of stock returns can be explained by the variable Return on Assets, Current Ratio, Debt Equity Ratio, Total Asset Turnover and Earnings per Share. Key words : Return on Asset, Current Ratio, Debt Equity Ratio, Total Aset Turnover , Earning per Share, Return Saham